Nilai-Nilai Pendidikan Akhlak terhadap Orang Tua dalam Q.S Luqman Ayat 14 - Fahrezi Yusron Huda; Eko Surbiantoro; Dewi Mulyani (UNISBA Press, 2021)
Abstract. As good Muslims, we must have perfect morals towards our people. Even in this day and age, there are many cases that are happening now to the murder of parents with trivial matters. From the above problems, the decline in morals and morals that should be something that should not be underestimated and should be prioritized, because moral education will be just decorative words in life without an application that is in accordance with real Muslim morals, namely akhlakul karimah as taught by Rasulullah SAW. This study uses a qualitative method, while the technique used in this research is a literature study/book survey by examining in depth various interpretations and books related to the main research problem. The content according to the mufassirins in supervising the QS. Luqman verse 14 explains how great the services and sacrifices of parents are that Allah SWT wills for every human being to do good to both of them. Regarding mother, she has gone to great lengths to produce and give birth as well as educate and nurture. From here a child should always do good for both parents and glorify parents and do not forget to always be grateful and grateful to both parents. Abstrak. Sebagai muslim yang baik, yaitu kita harus memiliki akhlak sempurna terhadap orang kita. Bahkan di zaman sekarang ini banyak terjadi kasus-kasus penganiayaan sampai pembunuhan terhadap orang tua dengan masalah sepele. Dari persoalan diatas bahwa kemerosotan akhlak dan moral yang seharusnya menjadi hal yang tak boleh dipandang sebelah mata dan harus diprioritaskan, karena pendidikan akhlak akan menjadi kata-kata hiasan saja dalam kehidupan tanpa aplikasi yang sesuai dengan akhlak muslim yang sesungguhnya yaitu akhlakul karimah seperti yang diajarkan oleh Rasulullah SAW. Penelitian ini menggunakan metode kualitatif, adapun teknik yang digunakan dalam penelitian ini adalah studi literature/book survey dengan mengkaji secara mendalam berbagai tafsir dan buku yang berhubungan dengan pokok masalah penelitian. Isi kandungan menurut para mufassirin dalam menafsirkan QS. Luqman ayat 14 menjelaskan begitu besar jasa dan pengorbanan orang tua sehingga Allah Swt mewasiatkan kepada setiap manusia untuk berbuat baik kepada keduanya terlebih pada ibu. Mengenai ibu, dia telah bersusah payah mengandung dan melahirkan serta mendidik dan mengasuh.